IMPACT OF PERCEIVED TALENT MANAGEMENT PRACTICES ON PYCHOLOGICAL CONTRACT OF EMPLOYEES IN BANKING SECTOR, SINDH, PAKISTAN - Qazi, Naira; Qureshi, Muhammad Nadeem; Kazi , Shazia; Kazi , Shazia; Anand, Viveke (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to evaluate the impact of employees’ perception of talent management on employer’s psychological contract in banking sector of Hyderabad and Mirpurkhas, Sindh, Pakistan. In addition to this, to determine the relationship of each (eight) perceived talent management practices with employer’s psychological contract. Self-administered survey was used to collect data from 233 high potential employees. Participants were selected using simple random sampling. Results revealed that perception of talented employees have strong positive impact on employer’s psychological contract. Moreover, all the perceived talent management practices have significant positive relationship with employer’s psychological contract individually.